Hi, I have this problem, but I am stuck in one thing.

Assuming that solutions to $\displaystyle y_{tt}=g(zy_z)_z$ are of the form $\displaystyle y(z,t)=Z(z)T(t)$, and that the separation constant is negative, written as $\displaystyle -v^2$ with $\displaystyle v>0$, I need to show that $\displaystyle Z(z)$ and $\displaystyle T(t)$ must satisfy the differential equations

$\displaystyle T''+v^2gT=0$, and

$\displaystyle zZ''+Z'+v^2Z=0$

So well, I kind know what to do once I have substituted $\displaystyle y(z,t)$ into $\displaystyle y_{tt}=g(zy_z)_z$... However, I keep on getting the wrong results:

I get this:

$\displaystyle Z(z)T''(t)=g(Z(z)Z'(z)T(t))_z$

$\displaystyle Z(z)T''(t)=g_z(T(t)(Z'(z)Z'(z)+Z(z)Z''(z)))$

But this is clearly not what should be on both sides :/

I would really appreciate it if any of you could give me a hand. Once I get both results on each side, I will be able to separate the variables.

Thanks a lot!